Freezing and melting of a colloidal adsorbate on a 1D quasicrystalline substrate - Schmiedeberg, Michael; Roth, Johannes; Stark, Holger (Physical Review Letters, 2006)
Using Monte Carlo simulations and an extended Landau-Alexander-McTague theory, we demonstrate that colloids in a one-dimensional quasicrystalline potential order in triangular and rhombic-alpha crystalline phases. Increasing the strength of the potential further, a new type of light-induced melting is discovered that has its origin in the nonperiodicity of the potential. In contrast to reentrant melting in periodic potentials, the quasicrystalline potential melts the crystalline phases even when they already exist at zero potential.